History and development prospects of silk farming in Uzbekistan - Nasirillaev Bakhtiyar; Rajabov Narzulla; Abdukadirov Murodkhuja; Fozilova Khurshida (E3S Web of Conferences, 2023)
Mulberry silkworm seeds were smuggled to Central Asia by a Chinese princess married to Khotan Khan in the middle of the 4th century. By the 7th century, Khotan, Kusham and other Northern Silk Industry was the main labor activity of the population in the provinces of Turkestan. In the 7th century, as a result of the introduction of the technology of cocooning and gazlam weaving by Marv merchants for commercial purposes from Persia, it became more widespread in the territory of Central Asia. Uzbekistan is a country with a long history among the world's developed silk industry. Mulberry silkworm seeds entered Central Asia through the Khotan province in the middle of the 4th century, and have become one of the main occupations of the population until now. This article analyzes the history of sericulture in Uzbekistan, stages of development, and achievements in the field of research and production. It is planned to increase the total area of mulberry plantations in Uzbekistan from 48,720 hectares in 2019 to 77,422 hectares by 2021, and the number of individual mulberry rows to 79 million 515 thousand bushes. It is also planned to increase the number of boxes of silkworms from 350,000 boxes to 500,000 boxes, from 19,607 tons to 30,000 tons.